Application of a Novel One-Side Cell Quartz Crystal Microbalance Immunosensor in the Determination of Alpha-Fetoprotein from Human Serum - Yan Chen; Huashan Shi; Bo Mu (Diagnostics, 2023)
The rapid and accurate detection of alpha-fetoprotein (AFP) levels is of great significance for the diagnosis and later treatment evaluation of liver cancer. In this study, a novel integrated quartz crystal microbalance (QCM) immunosensor based on the design to contact liquids on one side only was developed for the label-free detection of AFP. Anti-AFP mouse monoclonal antibodies were immobilized onto the upper electrode surface of the pre-treatment crystals using the staphylococcus aureus protein A. The AFP antigens in human serum were captured by specific surface-coated antibodies, and testing was carried out by monitoring the corresponding changes in frequency. The concentration range of the antigen detected was 13–760 ng/mL. The frequency characteristics of the process of antibody immobilization were investigated in detail, and high reproducibility of AFP antibody immobilization was achieved (standard deviation (SD) = 2.2 Hz). The developed QCM measurement system demonstrated a short test time (only 30 min), good reproducibility (the biological activity can still maintain more than 90% of the first test till it is reused five times), and accuracy as good as the one achieved with the radioimmunoassay (the maximum relative deviation = 4.8%). The designed QCM test system can easily and quickly detect AFP concentrations up to 760 ng/mL, indicating that the developed QCM assay is likely to lead to an alternative approach in large-scale screening for liver cancer in the near future.